ISOLASI BAKTERI DAN UJI AKTIVITAS ENZIM SELULOLITIK DARI SEDIMEN MUARA DAERAH ALIRAN SUNGAI SIAK WILAYAH KABUPATEN BENGKALIS DAN PERAIRAN DUMAI - Dian Permata Sari; Silvera Devi; Yuli Haryani (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Isolation of cellulolytic bacteria has been investigated because this bacteria producescellulase enzyme which has important role in various industry applications. In this research, isolation of cellulolytic bacteria was originated from sediment samples that was taken from 4 sampling points in estuary watershed of Siak River Bengkalis area and Dumai waters, which were 925 point (Siak River), 929 point (Pelabuhan Roro Pakning), 930 point (Bengkalis Strait), and 931 point (Dumai). Isolates of cellulolytic bacteria were identified with Gram staining method, the enzyme activities were measured with Nelson-Somogyi method. The results of identification showed 1 isolate was Gram positive and 15 isolates were Gram negative. The highest cellulase activity was obtained from 931-3S isolate (0.735±0.03) x 10 -3 U/mL, and it was not significant different with 929-1S, 929-2S, 929-3S, 930-3S isolates.